Influência da leptina na reatividade vascular em anéis de aorta de ratos obesos - Rocha, Vanessa da Silva (2015)
Obesity is a metabolic chronic disease characterized by excessive accumulation of body fat and an independent risk factor for development of cardiovascular disorders. Experimental studies show that the unsaturated high-fat diet-induced obesity promotes vascular alterations characterized by improved endothelial L-arginine/Nitric Oxide (NO) pathway. Research suggest that leptin is involved in this process, being able to promote vasodilation by increase of NO synthesis and/or release. The objective of this study was to evaluate the involvement of leptin on vascular reactivity in aortic rings of rats submitted to obesity by unsaturated high-diet fat. Thirty-day-old male Wistar rats were randomized into two groups: control (C, n=9) and obese (Ob, n=7). The C group was fed a standard diet and the Ob group was alternately submitted to four palatable high-fat diets for 27 weeks. Final body weight, total body fat and adiposity index were assessed. The glycemic profile was evaluated by glucose tolerance test (GTT) and systolic blood pressure (SBP) by tailcuff plethysmography method. The analysis of vascular reactivity was carried out in aortic segments and assessed by the concentration-response curves to phenylephrine (10-11 to 3x10-4 M), acetylcholine (10-12 to 10-4 M) and leptin (10-14 to 3x10-6 M) in the presence and absence of L-NAME (nonspecific inhibitor of NO synthase, 100 µM). Data were expressed using descriptive measures of variability position and submitted to Students T-test and two-way ANOVA followed by a Bonferroni post-hoc test. The level of significance was considered to be 5%. The results show that unsaturated high-fat diet used in this study promoted greater calorie intake, elevation of body weight and body fat, adiposity index, featuring a reproducible model of obesity. However, comorbidities frequently associated to experimental obesity were not visualized, such as glucose intolerance, dyslipidemia and hypertension. Obesity reduced the maximum response to phenylephrine (Rmax - C: 88.5 ± 4.8% vs Ob: 61.1 ± 5.4%*; p<0.05) and sensibility (pD2 - C: -6.78 ± 0.10 vs Ob: -7.31 ± 0.12 *; p<0.05). After incubation of aortic rings with L-NAME, in Ob group persisted significant decrease in pD2 (L-NAME/C: -7.41 ± 0.13 vs L-NAME/Ob: -7.80 ± 0.10# ; p<0.05) than C. Obesity lead did not change the vasodilation induced by acetylcholine between groups. However, after administration of L-NAME, the Rmax (L-NAME/Ob: 4.10 ± 1.89%# vs L-NAME/C: 26.54 ± 5.30%; p<0.05) was lower in the Ob group compared to C. Furthermore, the vasodilation induced by leptin in the presence and absence of L-NAME were not altered by obesity. In conclusion, obesity induced unsaturated fat diet leads to decreased contractile response without changing the vasodilator response. Furthermore, the findings show that leptininduced relaxation response is not altered due to the obesity, but are dependent on the release of NO.